ECONOMICAL WEED CONTROL IN LENTILS CROP - S. U. Chaudhary; J. Iqbal; M. Hussain; A. Wajid (Journal of Animal and Plant Sciences, 2011)
The effect of weed-management practices in lentil was studied through field experiments conducted during Rabi 2006-07 to 2008-09 at Adaptive Research Farm Gujranwala, Pakistan. The treatments studied were application of Stomp 330 E (pendimethalin) @3.25 lit/ha at seed bed preparation and just after sowing, respectively. Puma Super 7.5% EW (phenoxyprop-p-ethyle)@ 1.25 lit/ha as post emergence and two  hand hoeing at 30 and 60 days after sowing(DAS) compared with untreated plot. Hand hoeing gave higher weed control i.e. 95.77 and 98.12 % of broad and narrow leaved weeds, respectively and produced lowest weed dry matter (15.46 g/m2). Puma Super failed to control the broad leaved weeds. Application of Stomp at seed bed preparation was weak for the control of broad leaved weeds (61.04%) whereas narrow leaved weeds were controlled effectively (97.58%), but germination was affected. Highest grain yield (1519.56 kg/ha) was recorded from the plot with two hand hoeing. It gave maximum net income (Rs41247/ha) with a cost benefit ratio (CBR) of 1:5.16. Among the herbicides application of Stomp @ 3.25 lit/ha just after sowing + Puma super @ 1.25 lit/ha 45 DAS gave yield of 1415.67 kg/ha with 102.59 % increase in yield. It gave net income of Rs40093 /ha with a CBR of 1:13.73.
Keywords: Lentils (Lens culinaris); hand hoeing; herbicides; weed control; economics